Situational analysis of distal factors affecting early childhood care and development in the first 1000 days of life in Zamboanga del Norte - Michael Ralph M. Abrigo; Zhandra C. Tam (Philippine Institute for Development Studies (PIDS), 2019)
This study reports on the situational analysis conducted for Zamboanga del Norte as part of a larger study that aims to inform the development of strategies to improve early childhood care and development outcomes in KOICA-UNICEF intervention sites. A critical assessment of several underlying factors that are known to affect child nutrition outcomes highlights some of the key challenges present in Zamboanga del Norte that affect the availability, affordability, and accessibility of important interventions for child health and nutrition. We also highlight some local innovations and opportunities that may address some of the resource limitations that the province faces.
Keywords: 330; first 1; 000 days; early childhood care and development; Zamboanga del Norte; nurturing care practices; child nutrition